Health care Needs of Women Immediately Post‐Incarceration: A Mixed Methods Study. Issue 5 (5th March 2013) - Colbert, Alison M.; Sekula, L. Kathleen; Zoucha, Rick; Cohen, Susan M.
Abstract Objective(s) This study examined the health status of women with a recent history of incarceration and explored if/how women were accessing health care resources at the time immediately following release. Design and Sample This mixed methods study utilized two phases: (1) a quantitative survey; and (2) qualitative interviewing. Thirty‐four women (18 years of age and older, released from incarceration in the last 12 months) participated in the quantitative phase; 11 of those completed the qualitative interviews. Measures In phase 1, data were collected on demographics, health history, health status, and health‐promoting behaviors. In the second phase, semi‐structured interviews were used. Results Women in the study reported below average health status compared with the general population. The major health issues identified by participants included specific health problems affected by incarceration, mental health needs, routine health promotion and maintenance, recovery from substance abuse as a major health concern, and social and environmental barriers to care. Conclusions Women leaving jail or prison have significant and complex health care needs. This period of transition appears to be an opportune time to offer support, services, and other health‐promoting interventions.